Prevalence and risk factors for Lower Respiratory Tract Infection: a Multicenter study, at Kebbi State, Nigeria - Zaharaddin Muhammad Kalgo; Binta M. Amin; Bashir Muhammed; Habeeb K. Saka (International Journal of Advanced Health Science and Technology, 2023)
Lower respiratory tract infections are one of the major public health concerns responsible for morbidity and mortality in low and middle income countries. Improved surveillance of the causative agents as well as identification of risk factors might enable targeted intervention. The aim of this study was to establish the incidence and risk factors of lower respiratory tract infection in Kebbi State. Three hundred and fifty sputum samples were collected from consented patients with the symptoms of LRTI attending six different hospitals in Kebbi State. The samples were all screened for bacterial pathogens using standard microbiological techniques. The bacterial isolates were identified using conventional biochemical tests and then confirmed using commercial biochemical test kit microbact 24E (Oxoid UK) according to manufacturerer’s instruction. Staphylococcus aureus was the most predominant bacteria isolated in this location followed by Klebsiella pneumoniae with an estimated percentage occurrence of 31.1% and 22.2% respectively. Other bacteria isolated include Klebsiella oxytoca (13.9%), Escherichia coli (11.1%), Pseudomonas aeruginosa (5.6%), Aeromonas hydrophila (5.6%), Acinetobacter baumannii (4.6%), B. pseudomallei (2.8%) and Proteus spp (2.8%) in order of ranking. It was found out that, the young adults and the elderly were most at risk of a severe respiratory condition. The result also shows that LRTI were more common in males than in females. A significant number (32%) of patients who are exposed to either agricultural or industrial chemicals have positive bacterial growth. The present study found that prior antibiotic treatment was also a significant risk factor for LRTIs. In conclusion, it was found out that, Staphylococcus aureus is the most predominant bacteria isolated. Exposure to smoke from firewood and chemicals from both agricultural or industrial chemicals as well as indiscriminate use of antibiotics were the risk factors for LRTIs in this location.